Morphometric measurements and carcass characteristics of Black Australorp, Naked Neck, and Rhode Island Red crossbreds under alternative production systems - Usman,M. (2023)
Abstract The present trial explained the effect of alternative production systems on growth, morphometric and carcass traits of four different chicken genotypes. The second generation of two genotypes RNN (Rhode Island Red × Naked Neck) and BNN (Black Australorp × Naked Neck) obtained by two self-crosses (RNN × RNN = RR and BNN × BNN = BB) and two reciprocal crosses (RNN × BNN = RB and BNN × RNN = BR) were evaluated in three alternative production systems (conventional cages, enriched cages, and aviary). At the 6th week of age after sexing, a total of 600 birds, comprising 150 from each crossbred with a total of 300 pullets and 300 cockerels were divided into conventional cages, enriched cages, and aviary systems having 200 birds in each.Birds were organized into 3×4 factorial arrangements under Completely Randomized Design (3 production systems × 4 genotypes × 2 sexes × 25 birds = 600 birds). Regarding genotypes, RB and BR males showed higher (p < 0.01) carcass yield, drumstick weight, breast weight, and thigh weight than BB and RR genotypes. Females of BR genotype showed higher (p < 0.01) breast weight, thigh weight and drumstick weight. As far as production systems are concerned, higher (p < 0.01) liver weight, heart weight, breast weight, intestinal weight, drumstick weight, and thigh weight were observed in the males reared in enriched cages compared with conventional cages and aviary system. Females reared in enriched cages showed higher (p < 0.01) heart weight, breast weight, intestinal weight, drumstick weight, and thigh weight when compared with those reared in conventional cages and aviary. It is concluded that chickens (both sexes) of BR and RB genotypes had better morphological measurements and carcass traits than those of RR and BB genotype chickens. Among alternative production systems, chickens reared in enriched cages had better traits than those of reared in conventional cages and aviary during the growing phase.